2015
DOI: 10.4047/jap.2015.7.2.115
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the thread depth on the mechanical properties of the dental implant

Abstract: PURPOSEThis study aimed to evaluate the effect of implant thread depth on primary stability in low density bone.MATERIALS AND METHODSThe insertion torque was measured by inserting Ti implants with different thread depths into solid rigid polyurethane blocks (Sawbones) with three different bone densities (0.16 g/cm3, 0.24 g/cm3, and 0.32 g/cm3). The insertion torque value was evaluated with a surgical engine. The static compressive strength was measured with a universal testing machine (UTM) and the Ti implants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
5
21
0
Order By: Relevance
“…25 Although the limitations of this study were, tibia was chosen as the bone of choice, as it has very little cortical bone ranging from 3 to 4 mm which is why they measured top 3 threads for the percent osseointegration and the reason for low insertion torques. 33 depth increases primary stability and thus increasing the BIC which is in consensus with our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…25 Although the limitations of this study were, tibia was chosen as the bone of choice, as it has very little cortical bone ranging from 3 to 4 mm which is why they measured top 3 threads for the percent osseointegration and the reason for low insertion torques. 33 depth increases primary stability and thus increasing the BIC which is in consensus with our study.…”
Section: Discussionsupporting
confidence: 93%
“…32 But, a study by Sun-Young Lee concluded that deeper thread G RAPH 3 Comparison of mean values of BIC and BV between high torque 0.4 and 0.6 mm sized V-shaped implants depth increases primary stability and thus increasing the BIC which is in consensus with our study. 33…”
Section: Discussionmentioning
confidence: 99%
“…They found that outer and inner diameters are the most crucial factors for primary stability at the same implantation depth. Lee et al [18] evaluated the effect of thread depth on the primary stability of mini-implants in low-density bone. They showed that mini-implants with larger thread depth produced improved primary stability and higher RF value at the same inner diameter.…”
Section: Mini-implantsmentioning
confidence: 99%
“…[12,13] The implant system used in this specific trial (BT SAFE Bone Level Implants) has a specific implant body design with a quite accentuated morphology, which enables faster insertion, in conjunction with a double-thread design to direct the drilled bone immediately in contact with the surface of the implant.…”
Section: Resultsmentioning
confidence: 99%